Teacher instructional practices: untangling their complex relations with self-efficacy, job satisfaction, stress, and cooperation among mathematics teachers - Zakariya, Yusuf Feyisara; Adegoke, Nurudeen A. (Frontiers in Education, 2024)
Background: Teacher instructional practices play crucial roles not only in shaping the happenings in the classrooms but also in facilitating students' understanding and success rates in mathematics. However, previous studies on teachers' factors that bolster or undermine instructional practices often consider the influence of these factors on instructional practices in isolation.Objective: On the contrary, we took an inclusive approach in the present study to quantify and disentangle the complex relationship between self-efficacy, job satisfaction, stress, cooperation, and instructional practices with a focus on mathematics teachers.We used structural equation modelling to analyse the generated data from 1304 Norwegian secondary school mathematics teachers.The results showed that teacher self-efficacy contributes the most to teacher instructional practices through direct and mediating effects. It mediates the effects of stress and cooperation on teachers' practices. The contribution of teacher cooperation to instructional practices supersedes teacher stress while the effect of job satisfaction is not substantial. Also, instructional practices that include frequent use of techniques of cognitive activation, clarity of instruction, and classroom management are more prevalent among female than male mathematics teachers in Norway.By implications, these findings revealed that teacher self-efficacy and teacher cooperation are prime factors which interventions could bring about the desired improvement in classroom practices among mathematics teachers.